THE UTILIZATION OF ETHANOL EXTRACT OF THE SOURSOP LEAVES (Annona muricata L.) AS BREAST CANCER CHEMOPREVENTIVE - Karimah Ihda Husnayain; Asep Sukohar; Tiwuk Susantiningsih (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
The breast cancer is the highest incidence and causes of women mortality in the world. It is estimated every year that 12 million people suffering from the cancer and 7,6 million of them died. Cancer treatment includes surgery, radiotherapy and chemotherapy have more side effects. The preventions is needed to reduce the incidence of breast cancer. Then, a natural materials anticancer is needed as an alternative chemopreventive such as soursop (Annona muricata L.) which contains anticancer. The active substance in the soursop which is capable of acting as an anticancer is annonaceous acetogenins. Acetogenins in soursop leaves could selectively attack cancer cell growth. Acetogenins consist of active compounds that has cytotoxic activity which works by inhibiting the transport of adenosine triphosphate (ATP) in the mitochondria of breast cancer cells. The soursop leaf extract contains acetogenins as an anticancer agents that can prevent the growth of cancer cells that can not be controlled by the body's defense mechanism, so it can be concluded that the leaf extract of soursop can be used as an alternative chemopreventive against breast cancer. [J Agromed Unila 2014; 1(1):72-6] Keywords: acetogenins, breast cancer, soursop (Annona muricata L.)